Better understanding of project management amongst UiTM contractors / Hamimah Adnan … [et al.] - Adnan, Hamimah; Hashim, Norfashiha; Marhani, Mohd Arif; Yeop Johari, Mohd Asri (Research Management Institute (RMI), 2012)
The role of different project management techniques to implement projects successfully has been widely established in areas such as planning and control of time, cost and quality. Project management is the science and the art of planning, organizing and managing resources to bring the best achievement of specific project goals and objectives. Project management is a long term procedure needing the involvement of many persons and an efficient plan: without these, a project can end in chaos. This aim of this study is to provide a better understanding on the implementation of project management practice by UiTM contractors to ensure the success of project is guranteed without major problems occured. Thus, the purpose of this study is to identify the implementation of project management among UiTM contractor registered under Development Unit, UiTM. Questionnaires survey was distributed to 120 UiTM contractors and eight (8) indepth interview were held among the contractors. The purpose of this method is to gather information on their project background and also their project management skill. It was found that all of the contractors has a basic knowledge and understanding on project management skills.It is recommended that a reasonable project plan and appropraiate organisational structure to the stable implementation of a project. Contractors were recommended to produce their Key Performance indicators of the completed project. They need to have a good and proper programme of work and suitable project management system with an updated information system.